Hipopituitarismo causado por mutações no PROP1: Variabilidade fenotípica, importância diagnóstica e terapêutica - Pequeno, Thiago de Almeida (2016)
Introduction: Multiple pituitary hormone deficiency is characterized by the loss of two or more hormones of the pituitary action. Mutations in the gene PROP1 (Homeobox Protein Prophet of PIT-1) are the main genetic cause of these disorders. Objectives: to review the literature setting for genotype-phenotype relationships and to perform an epidemiological and clinical-genetic study of DMHH in Paraiba populations, discussing the issue of cost-effectiveness of using DNA sequencing techniques for diagnosis. Methods: using the descriptors "hypopituitarism", "homeodomain proteins", "genetics" and "hypopituitarism", "proteins homeodomain", "genetic" in addition to exclusion criteria, we selected 25 articles for review about DMHH caused by mutations in PROP1 gene published in PubMed, MedLine and Lilacs. In a cross-population-based study, 24 patients from seven communities of Paraiba were genotyped. Exons 1 to 3 of PROP1 gene, comprising the entire coding region, were amplified by PCR using intronic primers and sequencing by the Sanger method. The patients who were homozygote for mutation in PROP1 gene performed laboratory tests that assessed growth, thyroid function, sexual development and possible adrenal injury. Results: from data of literature, we verified that children, with short stature attended in primary care, should be investigated for GH, IGF1 and thyroid hormones levels. Confirming damage in producing of these hormones, it is important to test the genetic mutations in PROP1 gene for the purpose of establishing prognosis, avoiding surgery and imaging tests, and offering genetic counseling for family. In an epidemiological study, eight affected were identified among the 24 individuals with low stature, who were genotyped, and all shared the c.301_302delAG mutation in PROP1, indicating a cluster of disease in the community of Brejo do Cruz (PB) since all affected were related and kept tradition of inbreeding. Conclusions: Children with short stature and damage in thyroid hormones, GH, IGF1 should be tested for PROP1 mutations to determine the etiology of DMHH, especially in the backlands of Paraiba region.